Distribution and Production of N2O in the Subtropical Western North Pacific Ocean During the Spring of 2020 - Heo, Jang-Mu; Kim, Hyo-Ryeon; Eom, Sang-Min; Yoon, Joo-Eun; Shim, JeongHee; Lim, Jae-Hyun; Kim, Ju-Hyoung; Thangaraj, Satheeswaran; Park, Ki-Tae; Joo, HuiTae; Kim, Il-Nam (Frontiers in Marine Science, 2022)
Nitrous oxide (N2O) is an important greenhouse gas emitted in significant volumes by the Pacific Ocean. However, the relationship between N2O dynamics and environmental drivers in the subtropical western North Pacific Ocean (STWNPO) remains poorly understood. We investigated the distribution of N2O and its production as well as the related mechanisms at the surface (0–200 m), intermediate (200–1500 m), and deep (1500–5774 m) layers of the STWNPO, which were divided according to the distribution of water masses. We applied the transit time distribution (TTD) method to determine the ventilation times, and to estimate the N2O equilibrium concentration of water parcels last in contact with the atmosphere prior to being ventilated. In the surface layer, biologically derived N2O (ΔN2O) was positively correlated with the apparent oxygen utilization (AOU) (R2 = 0.48), suggesting that surface N2O may be produced by nitrification. In the intermediate layer, ΔN2O was positively correlated with AOU and NO3− (R2 = 0.92 and R2 = 0.91, respectively) and negatively correlated with nitrogen sinks (N*) (R2 = 0.60). Hence, the highest ΔN2O value in the oxygen minimum layer suggested N2O production through nitrification and potential denitrification (up to 51% and 25% of measured N2O, respectively). In contrast, the deep layer exhibited a positive correlation between ΔN2O and AOU (R2 = 0.92), suggesting that the N2O accumulation in this layer may be caused by nitrification. Our results demonstrate that the STWNPO serves as an apparent source of atmospheric N2O (mean air−sea flux 2.0 ± 0.3 μmol m-2 d-1), and that nitrification and potential denitrification may be the primary mechanisms of N2O production in the STWNPO. We predict that ongoing ocean warming, deoxygenation, acidification, and anthropogenic nitrogen deposition in the STWNPO may elevate N2O emissions in the future. Therefore, the results obtained here are important for elucidating the relationships between N2O dynamics and environmental changes in the STWNPO and the global ocean.